A new bacteriophage typing scheme forProteus mirabilis andProteus vulgaris strains: 3. Analysis of lytic properties - Sekaninová, G.; Rychlík, I.; Kolářová, M.; Pillich, J.; Seménka, J.; Zajícová, V. (Folia microbiologica, 1998)
The lytic properties of 21 bacteriophages constituting a new typing set forProteus were examined in 507Proteus mirabilis and 29P. vulgaris strains isolated from patients and healthy subjects. Comparison of their morphological, serological, genetic and lytic properties showed that, in theMyoviridae andPodoviridae families, some phages were so closely related that the presence of all of them in the set was redundant. Analysis of the lytic properties revealed that some of the bacteriophages were not active enough to facilitate the differentiation ofProteus strains The size of the final typing set was reduced from 21 to 12 phages but it was suggested that, in order to improve the differentiation capacity of the set, new phages should be included.